2021
DOI: 10.1021/acscatal.0c05255
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Pb Monolayer Deposition—Prelude for Further Advances in Catalyst Monolayer Synthesis via Surface Limited Redox Replacement Reaction

Abstract: We point out a novel opportunity for catalyst monolayer and core–shell structures synthesis via the surface limited redox replacement (SLRR) reaction. It is enabled by discovery of an electroless Pb monolayer deposition phenomenon whose fundamentals and practical aspects are presented. The particular benefit of this synthesis approach is for metal substrates which are not part of broadly conductive supports such as metal nanoparticles embedded in various oxides or zeolites. Examples of the catalyst monolayer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The underpotential deposition method is a surface-limited redox replacement reaction, which refers to the phenomenon that a metal is deposited on another substrate under the condition of a positive thermodynamically reversible potential, forming a deposition layer of atomic thickness [45]. The underpotential deposition (UPD) method can controllably synthesize metal nanocrystals and improve their catalytic performance, and can also modify the surface of metal electrodes at the atomic scale [46].…”
Section: Underpotential Deposition Methodsmentioning
confidence: 99%
“…The underpotential deposition method is a surface-limited redox replacement reaction, which refers to the phenomenon that a metal is deposited on another substrate under the condition of a positive thermodynamically reversible potential, forming a deposition layer of atomic thickness [45]. The underpotential deposition (UPD) method can controllably synthesize metal nanocrystals and improve their catalytic performance, and can also modify the surface of metal electrodes at the atomic scale [46].…”
Section: Underpotential Deposition Methodsmentioning
confidence: 99%
“…However, Brankovic et al . showed that a Pb monolayer can remain stable on a Au substrate electrode under inert conditions [25] . Therefore, to verify the stability of our Pb monolayer, we ran three different measurements.…”
Section: Resultsmentioning
confidence: 98%
“…[24] However, Brankovic et al showed that a Pb monolayer can remain stable on a Au substrate electrode under inert conditions. [25] Therefore, to verify the stability of our Pb monolayer, we ran three different measurements. First, a stripping CV was performed in a Pb-free solution under inert conditions (Figure 1 -red line, see also detailed description in SI section 3).…”
Section: Cupb 1ml Electrode Preparation and Characterizationmentioning
confidence: 99%